“Spotting” Mycobacterium bovis infection in leopards (Panthera pardus) – novel application of diagnostic tools - Gumbo, Rachiel; Goosen, Wynand J.; Buss, Peter E.; de Klerk-Lorist, Lin-Mari; Lyashchenko, Konstantin; Warren, Robin M.; van Helden, Paul D.; Miller, Michele A.; Kerr, Tanya J. (Frontiers in Immunology, 2023)
Background: Mycobacterium bovis (M. bovis) is the causative agent of animal tuberculosis (TB) which poses a threat to many of South Africa's most iconic wildlife species, including leopards (Panthera pardus). Due to limited tests for wildlife, the development of accurate ante-mortem tests for TB diagnosis in African big cat populations is urgently required. The aim of this study was to evaluate currently available immunological assays for their ability to detect M. bovis infection in leopards.Methods: Leopard whole blood (n=19) was stimulated using the QuantiFERON Gold Plus In-Tube System (QFT) to evaluate cytokine gene expression and protein production, along with serological assays. The GeneXpert ® MTB/RIF Ultra (GXU ® ) qPCR assay, mycobacterial culture, and speciation by genomic regions of difference PCR, was used to confirm M. bovis infection in leopards.Results: Mycobacterium bovis infection was confirmed in six leopards and individuals that were tuberculin skin test (TST) negative were used for comparison. The GXU ® assay was positive using all available tissue homogenates (n=5) from M. bovis culture positive animals. Mycobacterium bovis culture-confirmed leopards had greater antigen-specific responses, in the QFT interferon gamma release assay, CXCL9 and CXCL10 gene expression assays, compared to TST-negative individuals. One M. bovis culture-confirmed leopard had detectable antibodies using the DPP ® Vet TB assay.Preliminary results demonstrated that immunoassays and TST may be potential tools to identify M. bovis-infected leopards. The GXU ® assay provided rapid direct detection of infected 2 This is a provisional file, not the final typeset article leopards. Further studies should aim to improve TB diagnosis in wild felids, which will facilitate disease surveillance and screening.